Pharmacological effects of mTORC1/C2 inhibitor in a preclinical model of NASH progression - Arora, Mahak; Pavlíková, Zuzana; Kučera, Tomáš; Kozlík, Petr; Šopin, Tijana; Vacík, Tomáš; Ľupták, Matej; Duda, Matthias; Slanař, Ondřej; Kutinová Canová, Nikolina (Biomedicine & pharmacotherapy, 2023)
Knowledge of the benefits of mTOR inhibition concerning adipogenesis and inflammation has recently encouraged the investigation of a new generation of mTOR inhibitors for non-alcoholic steatohepatitis (NASH). We investigated whether treatment with a specific mTORC1/C2 inhibitor (Ku-0063794; KU) exerted any beneficial impacts on experimentally-induced NASH in vitro and in vivo. The results indicated that KU decreases palmitic acid-induced lipotoxicity in cultivated primary hepatocytes, thus emerging as a successful candidate for testing in an in vivo NASH dietary model, which adopted the intraperitoneal KU dosing route rather than oral application due to its significantly greater bioavailability in mice. The pharmacodynamics experiments commenced with the feeding of male C57BL/6 mice with a high-fat atherogenic western-type diet (WD) for differing intervals over several weeks aimed at inducing various phases of NASH. In addition to the WD, the mice were treated with KU for 3 weeks or 4 months. Acute and chronic KU treatments were observed to be safe at the given concentrations with no toxicity indications in the mice. KU was found to alleviate NASH-related hepatotoxicity, mitochondrial and oxidative stress, and decrease the liver triglyceride content and TNF-α mRNA in at least one set of in vivo experiments. The KU modulated liver expression of selected metabolic and oxidative stress-related genes depended upon the length and severity of the disease. Although KU failed to completely reverse the histological progression of NASH in the mice, we demonstrated the complexity of mTORC1/C2 signaling regulation and suggest a stratified therapeutic management approach throughout the disease course.
Keywords: mouse; non-alcoholic steatohepatitis; Ku-0063794; atherogenic diet; lipotoxicity; mTOR